2007
DOI: 10.1111/j.1551-2916.2007.01498.x
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of 200 nm BaTiO3 Particles with their Tetragonality 1.010 Via a Solid‐State Reaction Preceded by Agglomeration‐Free Mechanical Activation

Abstract: Well‐dispersed barium titanate (BaTiO3; BT) with an average primary particle size <200 nm and lattice tetragonality 1.010, being very close to that of a BT single crystal, was obtained via a solid‐state route with the aid of preliminary dry mechanical processing. The latter treatment not only activates the starting mixture but also decreases the particle sizes of individual ingredients and increases the homogeneity. All these favor to suppress grain growth of the product BT due to increasing nucleation site de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 14 publications
0
19
0
2
Order By: Relevance
“…A number of reports have described the synthesis of oxide powders by reducing the size of the starting materials, primarily as an initial attempt to reduce the firing temperature. [17][18][19][20][21][22][23] However, less information is available regarding the effects of reducing the individual raw material sizes on the initiation and completion temperatures or the reaction rate during mullite synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…A number of reports have described the synthesis of oxide powders by reducing the size of the starting materials, primarily as an initial attempt to reduce the firing temperature. [17][18][19][20][21][22][23] However, less information is available regarding the effects of reducing the individual raw material sizes on the initiation and completion temperatures or the reaction rate during mullite synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…BaCO 3 started to decompose and then Ba +2 ions diffused through the BaTiO 3 layer according to Eqs. In recent years, many researchers reported that ultra fine BaTiO 3 powders can be obtained directly, without the formation of the intermediate phase, Ba 2 TiO 4 , using a solid-state nanocrystalline BaCO 3 and TiO 2 reaction and mechanical activation [1][2][3][4][5][6][7][8][9][10][11][12][13]. Buscaglia et al [1] and Ando et al [2] considered using nano-crystalline BaCO 3 and TiO 2 as raw materials and mechanical activation can increase the homogeneity and contact points of the starting mixture, thereby promoting the reaction according to Eq.…”
Section: Second Stagementioning
confidence: 99%
“…However, a solid-state reaction occurring at higher temperatures easily leads to coarsening and agglomeration. Recently, a few researchers succeeded in preparing nano-sized BaTiO 3 powders using a solid state reaction below 1000 • C [1][2][3][4][5][6][7][8][9][10][11][12][13]. Therefore, the synthesis of nano-sized BaTiO 3 powder using a solid state reaction has becomes the research focus because of the lower cost, simpler process and higher productivity.…”
Section: Introductionmentioning
confidence: 99%
“…Reakcijom u čvrstom stanju nedavno je sintetisan BT sa prosečnom veličinom primarnih čestica od 200 nm, i tetragonalnošću od 1.010 [99]. Dodatnim mehanohemijskim tretmanom ne samo da se povećava homogenost polazne smeše već se i smanjuje veličina čestica.…”
Section: (B) Mehanohemijska Sintezaunclassified
“…Temperatura kalcinacije neophodna za sintezu BT reakcijom u čvrtstom stanju može da se snizi sa 1100 o C ako se prahovi prethodno mehanohemijski aktiviraju [99]. Pokazano je da ako se polazna smeša mehanohemijski tretira u planetarnom mlinu temperatura kalcinacije može da se snizi na 800 o C. Kao osnovni problem ostaje neizbežno smanjenje tetragonalnosti sa smanjenjem veličine čestica.…”
Section: (B) Mehanohemijska Sintezaunclassified